2020
DOI: 10.3390/ijerph17228646
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Ethylene Oxide Biomarker in an Exposed Residential Community

Abstract: The purpose of this study was to examine whether there is a difference in ethylene oxide (EtO) biomarker levels based on residential proximity to facilities emitting EtO, a carcinogen. We recruited residents living near two EtO-emitting facilities and administered a questionnaire on items such as address and length of residency, smoking habits, occupational exposures to EtO, and demographics. We also collected venous blood samples to measure an EtO biomarker, hemoglobin adduct N-2-hydroxyethyl-valine (HbEO), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…EO is a widely used industrial chemical for manufacturing various daily products such as antifreeze, polyester, detergents, adhesives, textiles, solvents, and pesticides. Exposure to EO in the general population may be through application of sterilized medical equipment ( 2 ), fumigation of food and cosmetics ( 3 ), and inhalation of contaminated air, tobacco smoke, and/or vehicle exhaust ( 4 , 5 ). Exposure to EO raises various health issues.…”
Section: Introductionmentioning
confidence: 99%
“…EO is a widely used industrial chemical for manufacturing various daily products such as antifreeze, polyester, detergents, adhesives, textiles, solvents, and pesticides. Exposure to EO in the general population may be through application of sterilized medical equipment ( 2 ), fumigation of food and cosmetics ( 3 ), and inhalation of contaminated air, tobacco smoke, and/or vehicle exhaust ( 4 , 5 ). Exposure to EO raises various health issues.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated peak 24 h exposure to EO caused in neighbourhoods close to a sterilisation facility in Michigan was assessed to be 1.83 µg/m 3 above the background level (Olaguer et al 2019 ), which in the United States is reported to vary between 0.18 and 0.4 µg/m 3 (0.1–0.22 ppb) (US-EPA 2020 ). In another report, residents living close to two EO emitting facilities in Illinois showed overall geometric Hb N -(2-hydroxyethyl)-valine adduct levels of 35.0 pmol/g Hb (29.7 pmol/g Hb for non-smokers) (Szwiec et al 2020 ), compared to an average (endogenous) background (Törnqvist et al 1989 ) of 20 pmol/g Hb reported earlier (Törnqvist et al 1989 ). Thus, occupational and environmental exogenous exposures to EO must be considered (Filser and Klein 2018 ).…”
Section: Process-related Contaminantsmentioning
confidence: 91%
“…Ethylene oxide (EtO) gas is a toxic industrial chemical that is widely used to sterilize medical equipment and to manufacture plastics, textiles, and antifreeze (U.S. EPA, 2022). While the extant literature has largely focused on adverse health effects resulting from occupational and hospital exposure, emerging evidence suggests that community members who live near EtO‐emitting facilities also show serious health outcomes (IDPH, 2019; Szwiec et al., 2020; U.S. EPA, 2023). Given the large number of EtO‐emitting facilities in the United States located in densely populated areas, understanding the comprehensive health risks associated with EtO exposure represents an urgent public health priority.…”
Section: Introductionmentioning
confidence: 99%